2013
DOI: 10.2147/ppa.s50970
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy for colorectal cancer: age differences in factors influencing patients' treatment decisions

Abstract: PurposeOlder colorectal cancer patients are significantly less likely than younger patients to receive guideline-recommended adjuvant chemotherapy. Previous research has indicated that patient refusal of treatment is a contributing factor. This study aimed to identify potential barriers to adjuvant chemotherapy use in older patients by examining the associations between patient age, factors influencing chemotherapy treatment decisions, and preferences for information and decision-making involvement.Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
(57 reference statements)
1
24
0
2
Order By: Relevance
“…With regards to age, the survival time of patients diagnosed with colorectal cancer in this study is lower than other study done in Netherlands [27]. The survival difference between young and older colorectal patients arises from different attributes of survival such as: difference in treatment modalities, the unfavorable effects of medication and intoxication, comorbidity in older patients, and low progression of disease in younger patients [28]. This could be due to lack of health awareness in receiving medical care, adherence to treatment during outpatient treatment and frequent follow-up constraint.…”
Section: Discussionmentioning
confidence: 55%
“…With regards to age, the survival time of patients diagnosed with colorectal cancer in this study is lower than other study done in Netherlands [27]. The survival difference between young and older colorectal patients arises from different attributes of survival such as: difference in treatment modalities, the unfavorable effects of medication and intoxication, comorbidity in older patients, and low progression of disease in younger patients [28]. This could be due to lack of health awareness in receiving medical care, adherence to treatment during outpatient treatment and frequent follow-up constraint.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study on colorectal cancer chemotherapy, which had a small number of patients and no adjustment for potential confounders, showed that younger patients preferred more information about the disease and chemotherapy and wanted to be more involved in treatment decisions. 32 …”
Section: Discussionmentioning
confidence: 99%
“…According to the TCR, five-year CSS among 20–39 year olds was, stage for stage, either comparable or superior to that of older age groups. Because younger cancer patients are, in general, more likely than older patients to receive aggressive antineoplastic therapy due to higher performance status, fewer comorbidities, and more willingness to accept risk, the superior survival among younger CRC patients in the TCR and other population-based studies may simply reflect selection bias rather than inherent tumor biology 38,39 . Indeed, a pooled analysis of 20,023 patients enrolled in randomized controlled trials for first-line stage IV CRC 40 revealed that, after adjustment for performance status and sex, the youngest patients (those near 18 years old) had inferior overall and progression-free survival when compared to middle-aged patients (those near 57 years old), especially during the first year of treatment.…”
Section: Discussionmentioning
confidence: 99%